Teacher Readiness for Implementing Deep Learning: A Case Study at GMIT Kuanino 1 Elementary School, Kupang - Intan Djo Wenyi; Maxsel Koro; Habibi Musa (Madako Elementary School, 2026)
Teachers' readiness in implementing deep learning is an important factor in improving the quality of learning in elementary schools, including at SD GMIT Kuanino 1 Kupang. This study aims to examine this readiness through a descriptive qualitative approach with a case study design. The research subjects were purposively selected classroom teachers, while data were collected through observation, interviews, and documentation, and then analyzed using an interactive model. The results of the study show that teachers in general have good readiness. This is reflected in the ability to design contextual learning, implement varied strategies, encourage active involvement of students, and reflect and provide feedback. Professionally, teachers are able to master the material, relate concepts, utilize simple media and technology, and understand the principles of meaningful and conscious learning. The obstacles faced include limited facilities and the need for sustainable competency development. These findings confirm that teacher readiness is adequate, but optimal implementation requires institutional support through strengthening school policies, provision of facilities, ongoing training, and professional mentoring so that in-depth learning can take place consistently and with quality.